Modeling and Control of a Thermally Driven MEMS Actuator for RF Applications - Estahbanati, Shahabeddin Vamegh (2017)
A Master of Science thesis in Electrical Engineering by Shahabeddin Vamegh Estahbanati entitled, "Modeling and Control of a Thermally Driven MEMS Actuator for RF Applications," submitted in May 2017. Thesis advisor is Dr. Rached Dhaouadi and thesis co-advisor is Dr. Maher Bakri-Kassem. Soft and hard copy available.